The adjusting with university life and its relation to some variables among the students of the University of hostedAl-Furatin Tishreen University in the shadow of the Syrian crisis - Al Akhras, Sumaya (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
this study aims Specifying the level of adjusting with university life among the students of the University of Al-Furat hosted at Tishreen University after leaving their mother university due to the current security conditions experienced by Syria through some variables such as gender , study specialization and place of residence. In order to answer the study questions and verify their hypotheses, the researcher applied a measure of adjusting with university life on a sample of the students of the University of Al-Furat who were hosted at Tishreen University. The number of students in the sample (332) , The results of the study showed the following: The social adjusting came in first place and the psychological adjusting In the second place and the academicadjusting in the third place, and there are differences of statistical significance in the axis of psychological adjusting according to gender variable and these differences in favor of females, while there were no differences in the axes of social and academic adjusting according to gender variable, and the research there are differences of statistical significance in the axis of social adjusting The differences were found in favor of the humanitarian faculties, while there were no differences in the pivotal psychological and academic adjusting. There were also statistically significant differences in the level of psychological adjusting between the students according to the variable of the place of residence, The differences were found in favor Of those( who live in the houses with the family),There is relationship statistically significant correlation betweenaxes The adjusting with university life and variables(gender, academic specialization, the place stay). This study offered some propositions.